Karakteristik pada Obesitas Berdasarkan Rentan Umur di Kelurahan Nganganaumala Kota Bau-Bau - Armanto Makmun; Indri Meliawati Radisu (Indonesian Journal of Health, 2021)
Background and Purpose: Obesity is an imbalance in the amount of food intake compared toenergy expenditure carried out by the body. Some of the factors that cause obesity include lifestyle,diet, and physical activity. Obesity in adulthood has an impact on health, where weight gain andobesity are risk factors for increasing the incidence of non-communicable diseases. The purpose ofthis study was to determine the relationship between age vulnerability and the incidence of obesity.Methods: This study is a descriptive research design. Data collected using a questionnaire. The dataof this study were categorical variables from 2 groups so that it used the Chi-Square test. Referencesearch results are entered into the Mendeley app using the system Vancouver. Results: The totalsample size of 98 people with adolescence 11-19 years 7 people (7.1%), adults 20-60 years 88 people(89.8%), elderly> 60 years 3 people (3.2%) . Based on gender, it was found that 18 men (18.4%) and80 women 81.6%). And based on BMI, it was found that 19 people were underweight (19.4%), normal41 people (41.8%), overweight 12 people (12.2%), obese 1 23 people (23.5%), and obese 2 3 people(3.1%). Conclusion: There is no relationship between age susceptibility to obesity.